Stone Cold : The Extraordinary Story of Len Opie, Australia's Deadliest Soldier. - Faulkner, Andrew (Sydney : Allen & Unwin, 2016)
From the jungles of New Guinea to the CIA's black ops program in Vietnam, this is the extraordinary life of one of Australia's fiercest soldiers.
Cover -- Title -- Copyright -- Dedication -- Contents -- List of maps -- List of abbreviations -- Introduction -- 1 A warrior in training -- 2 Up the Ramu -- 3 Balikpapan -- 4 Korea -- 5 The Third World War has started! -- 6 Hills are for heroes -- 7 Kapyong -- 8 Kill or be killed -- 9 Maryang San -- 10 Private, temporary corporal, temporary warrant officer, class two -- 11 Eyes like a cat and no nerves at all -- 12 Belles and bullies -- 13 Vietnam -- 14 On the trail -- 15 'Sneaky work': the Phoenix program -- 16 Kashmir interlude -- 17 Return to Vietnam -- 18 Man of Sparta -- PIC SECTION -- Len Opie's medals -- Acknowledgements -- Notes -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Opie, Len,-1923-2008.; Australia.-Australian Army.-Royal Australian Regiment.-Battalion, 3rd.; Soldiers-Australia-Biography.; Electronic books